ANALISIS GENDER TERHADAP STRATEGI KOPING DAN KESEJAHTERAAN KELUARGA (Gender Analysis Toward Coping Strategies and Family Well-Being) - Herien Puspitawati; Tin Herawati; Ma'mun Sarma (Sosio Konsepsia, 2010)
In order to increase the gender roles in many aspects of familyÂ livelihood, and to increase the socioeconomic and cultural well-being of the family and community level, this study aims to: (1) Analyze the characteristics and family economic sufficiency, (2) Analyze the gender roles in decision making and implementation of coping strategies, and (3) Analyze factors affecting family well-being. The advantages of this study are for the development of family studies from gender analysis perspective and for the inputs of family counseling needs. The study was conducted at Hambaro Village, Sub-District of Nanggung, District of Bogor-West Java Province in April to August 2008, by using a cross sectional study design. The location of study was chosen purposively. The samples were 110 Janner families through systematically randomsampling method. The result showed that the average of the wife's education was low, with the length of education was 4.4 years. Almost half of the housewives were not working, and more than three-quarter of the husband were fanners. The average of monthly income per capita was Rp. 133.778,82, and the average of monthly expenditure per capita was Rp. 161.142,96. Roughly speaking, gender roles in decision making and implementation of the family (as the composite factors of management aspect, a cutting back expenses strategy, and a generating income strategi;) based on the gender partnership with the degree of intermediate level. Finally, it was found that family subjective well-being was influenced indirectly by the high husband's education level, the low family economic sufficient level, and the low partnership of gender roles in decision making of coping strategies.